Comparison of silver-plated nylon (Ag/PA66) e-textile and Ag/AgCl electrodes for bioelectrical impedance analysis (BIA). (21st April 2021) - Logothetis, Irini; Gil, Ignacio; Wang, Xungai; Razal, Joselito
Abstract: Recently, researchers have adapted Bioelectrical Impedance Analysis (BIA) as a new approach to objectively monitor wounds. They have indicated various BIA parameters associated to specific wound types can be linked to wound healing through trend analysis relative to time. However, these studies are conducted using wet electrodes which have been identified as possessing several shortcomings, such as unstable measurements. Thus, the adaption of e-textile electrodes has become an area of interest in measuring biosignals. E-textile electrodes are known to possess a significantly large polarization impedance ( Z p ) that potentially influences these biosignal measurements. In this study we aim to identify the suitability of e-textile electrodes to monitor wounds using BIA methodologies. By adapting suggested methodologies conducted in-vivo from previous studies, we used an ex-vivo model to observe the behaviour of e-textile electrodes relative to time. This was compared to common clinical wet electrodes, specifically Ag/AgCl. The objective of this study was to identify the BIA parameters that can be used to monitor wounds with e-textile electrodes. By analysing the BIA parameters relative to time, we observed the influence of Z p on these parameters.